Integrasi Kearifan Lokal dalam Pembelajaran Sejarah: Tinjauan atas Kurikulum Merdeka - Siregar, Muhammad Andre Syahbana; Suboh, Amerruddin Shah (Medan Resource Center, 2025)
This article aims to examine the integration of local wisdom in history education, focusing on the review of the implementation of the